Research and Analysis on Assembly Methodology for the Fusion Blanket System. (21st September 2022) - Zhang, Ruonan; Li, Jiazhu; Xu, Shuling; Wu, Qigang; Yu, Dawei; Man, Qiankun
Abstract : In the development process of the blanket system, assembly design is quite important, and suitable systematic methodologies are required. As we know, the CFETR machine and the associated fusion components are not usually mass-produced large-scale products, but highly customized machines which are still in the design phase. Appropriate assembly methodology plays an important role in fulfilling the function of the fusion machine. This paper has investigated some universal assembly methods for similar complex products. Two preferred methods of design-for-assembly (DFA) and product-process hierarchical modeling (PPHM) have been analyzed and improved taking the fusion blanket system as a study case. The overall process of the blanket system was studied including the stages of design, assembly, and overview of the blanket system hierarchy structure. The two newly proposed methods aim to clarify a probably feasible assembly method for the blanket system, though it is still in the engineering design stage. Case studies of the two favorable assembly methods can be good references to demonstrate and analyze the advantages of DFA and PPHM for decision-making in each product development phase.